2015
DOI: 10.1002/gj.2708
|View full text |Cite
|
Sign up to set email alerts
|

Dip variations of the North American and North Caribbean Plates dominate the tectonic activity of Puerto Rico–Virgin Islands and adjacent areas

Abstract: The M 7.0 Haiti earthquake of 2010 in the Greater Antilles is a reminder that the northeastern Caribbean is at a high risk for seismic and tsunami hazards. The Greater Antilles consist of the Hispaniola microplate to the west and Puerto Rico–Virgin Islands to the east and are situated between two subduction zones with the Puerto Rico Trench to the north and the Muertos Trough to the south. Although there is no active volcanism on Puerto Rico, earthquake depths and previous seismic tomography results imply that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…We have carried out an exhaustive search for data and geomagnetic surveys in the study area and, although no new works have been found, similar or related works have been carried out in the environment of the study area: magnetic mapping of the northern Caribbean region using marine magnetic data from GEODAS [55], works about gravity and magnetic field referring to hydrocarbon prospects at the Tobago Basin [56], geological description and interpretation in Providencia and Santa Catalina Islands [57], and many others related to tectonics and volcanism [58,59].…”
Section: Resultsmentioning
confidence: 99%
“…We have carried out an exhaustive search for data and geomagnetic surveys in the study area and, although no new works have been found, similar or related works have been carried out in the environment of the study area: magnetic mapping of the northern Caribbean region using marine magnetic data from GEODAS [55], works about gravity and magnetic field referring to hydrocarbon prospects at the Tobago Basin [56], geological description and interpretation in Providencia and Santa Catalina Islands [57], and many others related to tectonics and volcanism [58,59].…”
Section: Resultsmentioning
confidence: 99%